Dawes's Budget of the United States - Fairchild, Fred Rogers; Dawes, Charles G. (Quarterly Journal of Economics, 1924)
Journal Article Dawes's Budget of the United States Get access Fred Rogers Fairchild Fred Rogers Fairchild Yale University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 38, Issue 2, February 1924, Pages 338–343, https://doi.org/10.2307/1884016 Published: 01 February 1924